2001
DOI: 10.1023/a:1005638900581
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Aristotle's doctrine on causation identifies four distinct types of cause: formal, efficient, material, and final. Science is said to have differentiated itself from philosophy by concentrating solely on efficient causes. Nonetheless, when applied to narratives of causation, Aristotle's doctrine provides a useful heuristic to explore the issues such as Aboriginal and biomedical perceptions of causal factors for non-insulin dependent diabetes mellitus (NIDDM) on Manitoulin Island, Ontario. This paper also outli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Due in part to such findings, some have argued that an effective strategy for improving the mental health of American Indian adolescents is through involvement in traditional activities and ceremonies of their heritage and culture. Enculturation, the process of socialization to and maintenance of the norms of one’s indigenous community (Kim & Abreu, 2001; Kim & Omizo, 2006), has been shown to provide a mechanism for coping with acculturative stress (LaFromboise, Hoyt, Oliver, & Whitbeck, 2006; Sunday, Eyles, & Upshur, 2001; Zimmerman, Ramirez-Valles, Washienko, Walter, & Dyer, 1996); indeed, this is one of the assumptions on which the relatively recent “retraditionalization” movement is based. In his study on the treatment of substance abuse among First Nation people, for instance, McCormick (2000) found that reconnection to cultural traditions helped them discover meaning in life.…”
mentioning
confidence: 99%
“…Due in part to such findings, some have argued that an effective strategy for improving the mental health of American Indian adolescents is through involvement in traditional activities and ceremonies of their heritage and culture. Enculturation, the process of socialization to and maintenance of the norms of one’s indigenous community (Kim & Abreu, 2001; Kim & Omizo, 2006), has been shown to provide a mechanism for coping with acculturative stress (LaFromboise, Hoyt, Oliver, & Whitbeck, 2006; Sunday, Eyles, & Upshur, 2001; Zimmerman, Ramirez-Valles, Washienko, Walter, & Dyer, 1996); indeed, this is one of the assumptions on which the relatively recent “retraditionalization” movement is based. In his study on the treatment of substance abuse among First Nation people, for instance, McCormick (2000) found that reconnection to cultural traditions helped them discover meaning in life.…”
mentioning
confidence: 99%
“…Research on diabetes, conducted in the Opaskwayak Cree Nation in Manitoba and two Anishnaabe communities in Ontario, found that health care providers attributed diabetes to individual lifestyle factors and thus undergird personal responsibility, whereas individuals in the community viewed diabetes as being rooted in collective and historical experiences and tied to a sense of powerlessness (Bruyere & Garro, 2000; Sunday, Eyles, & Upshur, 2001). In our study, we did not explore narratives of health care providers, but as far as the participants were concerned, there was no such sharp division between the biomedical and collective cardiac narratives.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that enculturation may not universally function as a protective mechanism (De Coteau, Hope, & Anderson, 2003;LaFromboise, Medoff, Lee, & Harris, 2007), a larger body of research suggests that enculturation is a mechanism for coping with acculturative stress (LaFromboise, Hoyt, Oliver, & Whitbeck, 2006;Sunday, Eyles, & Upshur, 2001;Zimmerman, Ramirez-Valles, Washienko, Walter, & Dyer, 1996), facilitating healing (Iwasaki, Bartlett, & O'Neil, 2005), and discovering meaning in life (McCormick, 2000). A number of studies suggest that bicultural competence encourages healthy coping strategies and positive mental health outcomes (Bankston & Zhou, 1997;Berry, 1997;Berry, Phinney, Sam, & Vedder, 2006;Phinney et al, 2001;Suinn, Rickard-Figueroa, Lew, & Vigil, 1987;Garrett & Carroll, 2000;Whitbeck, Hoyt, McMorris, et al, 2001;LaFromboise et al, 2010).…”
Section: American Indian Identitymentioning
confidence: 99%